A Treat-and-Extend Regimen of Intravitreal Brolucizumab for Exudative Age-Related Macular Degeneration Refractory to Aflibercept: A 12-Month Result - Wataru Kikushima; Yoichi Sakurada; Yoshiko Fukuda; Mio Matsubara; Yumi Kotoda; Atsushi Sugiyama; Kenji Kashiwagi (MDPI AG, 2023)
We aimed to investigate whether a treat-and-extend regimen of intravitreal brolucizumab (6.0 mg/0.05 mL) is effective for eyes with exudative age-related macular degeneration (AMD) refractory to aflibercept for 12 months. Sixty eyes from 56 patients receiving brolucizumab for exudative AMD refractory to aflibercept were included. Patients received a mean of 30.1 aflibercept administrations for a mean 67.9-month follow-up. All patients exhibited exudation on optical coherence tomography (OCT) despite regular 4-8 weeks of aflibercept administration. Visit 1 was scheduled at the same interval from the last aflibercept injection to the baseline. The treatment interval was extended or shortened by 1-2 weeks depending on the presence or absence of exudation on OCT. After switching to brolucizumab, the follow-up interval significantly extended at 12 months (before switching: 7.6 ± 3.8 weeks vs. at 12 months: 12.1 ± 6.2 weeks, p = 1.3 × 10−7). Forty-three percent of the eyes achieved a dry macula at 12 months after switching. However, the best-corrected visual acuity did not improve at any visit. Morphologically, the central retinal thickness and subfoveal choroidal thickness significantly decreased from baseline at 12 months (p = 3.6 × 10−3 and 1.0 × 10−3, respectively). Switching to brolucizumab can be considered to extend the treatment interval in eyes with exudative AMD refractory to aflibercept.